Synthesis of some transition metal complexes of novel 1-methylpyrazole-3-aldehyde-4-(2-pyridyl) thiosemicarbazone: Spectroscopic and in vitro biological activity studies - Aljahdali, Mutlaq Shedeed; Elmalik, Yahia Hassan; El-Reash, Gaber Mohamed Abu (European Journal of Chemistry, 2014)
Four new mixed ligand metal(II) complexes with 1-methylpyrazole-3-aldehyde-4-(2-pyridyl)thiosemicarbazone (MPAPT) and 1,10-phenanthroline are reported. These complexes namely Cu(MPAPT)(1,10-phen)(Cl)] (1), [Ni(MPAPT)(1,10-phen)(Cl)] (2), [Mn(MPAPT)(1,10-phen)(Cl)].H2O (3) and [Co(MPAPT)(1,10-phen)(Cl)].H2O (4), were characterized by elemental analysis, spectral (IR, 1H NMR and UV-Vis) and magnetic moment measurements. The magnetic and spectral data indicates octahedral structure for all complexes. Metal complexes have been modeled using parameterized PM3 semi-empirical method. The free ligand and its M(II) chelates have been screened for their antimicrobial activities. The antimicrobial screening demonstrated that, the Cu(II) complex have the maximum and broad activities among the investigated complexes.